Mapping the terrain of public service quality improvement: twenty-five years of trends and practices in the United State - Holzer, Marc; Kim, Younhee; Charbonneau, Etienne (2009)
The quality movement in the United States has been characterized as an impetus for organizational effectiveness and responsiveness since the late 1970s. `Quality' can be a subjective term as each organization has its own definition and boundaries. Three emphases are evident in the field of quality improvement: quality circles, total quality management, and citizen satisfaction. Practices of quality improvement in the public sector have been driven by demands from citizens for more effective services, outcomes that require the implementation of suitable quality models and standards. - Reproduced.
Keywords: Public administration